Speeding Up the Internet: Regulation and Investment in European Fiber Optic Infrastructure - Wolfgang Briglauer; Carlo Cambini; Michał Grajek (International Telecommunications Society (ITS), 2017)
In this paper, we study how the coexistence of access regulations for legacy (copper) and fiber networks shapes the incentives to invest in network infrastructure. To this end, we develop a theoretical model explaining investment incentives by incumbent telecom operators and heterogeneous entrants and test its main predictions using panel data from 27 EU member states over the last decade. Our theoretical model extends the existing literature by, among other things, allowing for heterogeneous entrants in internet access markets, as we consider both other telecom and cable TV operators as entrants. In the empirical part, we use a novel data set including information on physical fiber network investments, legacy network access regulation and recently imposed fiber access regulations. Our main finding is that more stringent access regulations for both the legacy and the fiber networks have, in line with our theoretical model, an asymmetric effect on incumbent telecom and cable TV operators; both harm investments by the former, but do not affect the latter.
Keywords: L96; L51; 330; Internet access market; Access regulation; Investment; Infrastructure; Next Generation Networks; Broadband; Telecoms; Cable operators and Europe